STUDENTS' STRATEGIES IN UNDERSTANDING ENGLISH TEXTS IN ADVEN CLASSES OF SORONG CITY - Masan, Agustinus Lia; Kelelufna, Vantri Pieter; Suripaty, Roberthair (J-mace : Jurnal Penelitian, 2025)
This study explores the strategies used by students of SMA Advent Kota Sorong in comprehending English texts. In the era of globalization, the ability to comprehend English texts is the key to academic and communication success. Qualitative research methods with data collection through interviews and observations were used to identify students' learning strategies. The results showed that students relied on techniques such as skimming, scanning, content prediction, and use of context to improve comprehension. In addition, metacognitive strategies such as planning and self-evaluation were also found to play an important role. A supportive learning environment and high motivation strengthened the effectiveness of these strategies. These findings provide important insights for educators to develop more innovative and student-oriented learning approaches. This study is expected to improve the quality of English learning at SMA Advent Kota Sorong.